2022
DOI: 10.1029/2022ja030627
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Angle Distribution of MeV Electrons in the Magnetosphere of Jupiter

Abstract: The magnetosphere of Jupiter harbors the most extreme fluxes of MeV electrons in the solar system and therefore provides a testbed of choice to understand the origin, transport, acceleration, and loss of energetic electrons in planetary magnetospheres. Along this objective, the Pitch Angle Distribution (PAD) of energetic electrons may reveal signatures of the dominant physical processes. Here, we analyze for the first time the PAD of MeV electrons observed by the Galileo‐Energetic Particle Detector (EPD) exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…To constrain the robustness of our results, we now investigate how including an anisotropic PAD would alter the surface influx maps of energetic electrons. Observations by the Galileo and Juno spacecraft (e.g., Ma et al., 2021; Nénon et al., 2022) suggest that the PAD of energetic electrons near Europa changes with time and magnetic latitude, and varies between isotropic and pancake distributions (i.e., with higher particle fluxes near pitch angles of 90° and fewer near 0° and 180°). We therefore calculated maps of the surface number flux of energetic electrons using a pancake PAD (∝ sin( α ), where α is the pitch angle).…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To constrain the robustness of our results, we now investigate how including an anisotropic PAD would alter the surface influx maps of energetic electrons. Observations by the Galileo and Juno spacecraft (e.g., Ma et al., 2021; Nénon et al., 2022) suggest that the PAD of energetic electrons near Europa changes with time and magnetic latitude, and varies between isotropic and pancake distributions (i.e., with higher particle fluxes near pitch angles of 90° and fewer near 0° and 180°). We therefore calculated maps of the surface number flux of energetic electrons using a pancake PAD (∝ sin( α ), where α is the pitch angle).…”
Section: Model Resultsmentioning
confidence: 99%
“…Energetic electron pitch angle distributions (PADs) within the Jovian magnetosphere vary strongly with both magnetic latitude and radial distance. Galileo and Juno observations (e.g., Ma et al., 2021; Nénon et al., 2022) show that the PAD near Europa varies with the time of observation and magnetic latitude between nearly‐isotropic and pancake distributions (which feature the maximum flux near pitch angles of 90°). For our study, we treat the energetic electron PAD at Europa as isotropic.…”
Section: Modeling Energetic Electron Influx Onto Europamentioning
confidence: 99%
“…To convert the allowed particle trajectories into fluxes onto the moon's atmosphere, we assume that the ambient electron and ion pitch angle distributions are isotropic in the plasma near Callisto. Nénon et al (2022) have recently shown this approximation to be valid for electrons above energies of 1 MeV near this moon, and observations of energetic ions by the Galileo EPD are roughly isotropic at Callisto's orbital position (Mauk et al, 2004). At Europa, anisotropies in the magnetospheric energetic ion distribution only affect the resulting fluxes onto the moon quantitatively, reducing the total flux by approximately 10% (Addison et al, 2021).…”
Section: Calculating Energetic Particle Fluxes Onto Callisto's Atmosp...mentioning
confidence: 94%
“…Among these, PADs constitute minor effects on the scatter for measurements near the equatorial plane, such as those made by Galileo. This is because that PADs are flat compared with the energy distributions at low latitudes in the M-shell range concerned here (Nénon et al, 2022;Tomás et al, 2004).…”
mentioning
confidence: 85%